Approximate method for the solution of the generalized Dirichlet problem - Lopushanskaya, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We extend the method for approximate solution of classical boundary-value problems for the Laplace equation suggested in [1–3] to the case of the Poisson equation with generalized functions on the right-hand side of the equation and in the boundary conditions.